Kinerja Profesional Guru Pada SMA Negri Kota Ternate - Irsan Habsyi; Bustanul Arifin (Jurnal Ilmiah Wahana Pendidikan, 2023)
The focus of this research is: Professional Performance of Teachers in State Senior High Schools in Ternate City. Based on the focus of the research, the problems were formulated: (1) How is the Professional Performance of Teachers of SMA Negeri Kota Ternate (2) What factors hinder the professional performance of teachers of SMA Negeri Kota Ternate (3) What efforts are made to overcome the factors that hinder the professional performance of teachers of SMA Negeri Kota Ternate. This research uses research methods that are based on holistic, complex, dynamic, and meaningful. The data collected is not numerical but qualitative. The results of this study are: (1) Professional Performance of Teachers of State Senior High School of Ternate City is good (2) Factors that hinder the professional performance of teachers of State Senior High School of Ternate City are based on the data obtained that there is still a lack of facilities and infrastructure, the teacher's late step to school. There are several teachers in the mastery of making lesson plans and syllabus is still minimal. IT mastery in order to educate students better and get quality that can compete with other regions. (3) Efforts made to overcome the factors that hinder the professional performance of teachers in public high schools in Ternate City, namely the need for cooperation with the government and schools in Ternate City. Coordinating with the government so that there is serious attention to the development of SMA Negeri Kota Ternate. Based on these conclusions, it is recommended that: (1) commitment as a teacher should be followed by high enthusiasm in advancing themselves by adding books supporting lessons. (2) it is necessary to collaborate with the government and with schools in Ternate City to overcome the lack of facilities and infrastructure so that students do not miss the subjects taught by teachers. (3) the principal should provide guidance and motivation that can spur the spirit of the teachers.